MENINGKATKAN LITERASI DAN NUMERASI BERBASIS BIMBEL KEPADA SISWA SD NEGERI NO. 102058 DOLOK MASIHUL - Carolina Pakpahan; Marsaulina Samosir; Marsaulina Br. Aruan; Laura Thresia Manalu; Helmi Artini Damanik; Nomi Noverita Sinaga; Lexmana Sihombing (COVIT (Community Service of Health), 2022)
The purpose of this Community Service (PkM) program is to learn about the process of making child-friendly school-based reflective module products that can improve numeracy literacy skills and self-confidence in elementary school students in Dolok Masihul District in grades IV, V, and VI. This activity is carried out by the Serdang Bedagai II team and is carried out every Monday to Wednesday. The PkM activity was held from February 2 – 26, 2022 at SDN 102058 Dolok Masihul. The target of this PkM program is students in grades IV, V and VI of SDN 102058 Dolok Masihul. The form of activities in the implementation of this service includes free tutoring activities for English, Mathematics, Indonesian and PkN subjects which are carried out at SDN 102058 Dolok Masihul. The impact of the implementation of this PkM activity is 1) Produce reflective modules based on child-friendly schools that are ideal for strengthening numeracy literacy abilities and self-confidence of Dolok Masihul District grade IV, V, and VI primary school pupils, 2) Knowing the impact of child-friendly school-based reflective modules on numeracy literacy abilities and self-confidence in Dolok Masihul District grade IV, V, and VI primary school pupils. Keywords: Literacy, numeracy, tutoring, improvement